PENENTUAN BATAS DESA MELALUI PENDEKATAN PARTISIPASI MASYARAKAT DI DUSUN SENAMAT ULU KECAMATAN BATHIN III ULU KABUPATEN BUNGO PROVINSI JAMBI - muhammad arfan latanza; Yurni Suasti; endah Purwaningsih (JURNAL BUANA, 2019)
This study aims to know : (1) The process and stages of determining village boundaries through a community participation approach in the Senamat Ulu village, Bathin III Ulu District. (2) Creating administration map for Senamat Ulu village, Bathin III Ulu District. This type of research is classified into a descriptive study with a qualitative approach. This study uses Participatory Rural Appraisal method with participatory mapping techniques and Focus Discussions Group to gather information about the Senamat Ulu village boundaries and involve direct community participation in the stages and process of determining Senamat Ulu village boundaries. From this research, the results of the study are as follows: (1) the process and stages of determining village boundaries through the community participation approach in the Senamat Ulu village are divided into 3 processes and stages, namely a. stage of determining village boundaries, b. search stage and village boundary data collection survey, and c. the stage of processing village boundary survey data. (2) From the 3 stages of determining village boundaries through the community participation approach the results are Administration Map of Senamat Ulu village.